Rancang Bangun Alat Pengering Helm Berbasis QFD beserta Analisis Keuangan - Kamal, Naufal Izzul; Riskianto, Aldinu; Pradana, Raihan Yufi; Akhyar, Muhammad Faiq Nadhliful; Nugroho, Dony Satriyo (Fakultas Teknik Universitas Tulang Bawang, 2025)
UMKM Helmet and Care is a type of business engaged in the field of helmet-washing services. The helmet drying process is still done manually, resulting in the business process not being able to run optimally. So a solution is needed in the form of a helmet dryer that suits the needs of UMKM. The design of the helmet dryer using the QFD method resulted in the helmet dryer being equipped with a DHT22 sensor and a Thermostat sensor. , the material used is Stainless Steel, the price of the helmet dryer is IDR 5,500,000, the dimensions of the tool are based on worker anthropometry, namely 140 cm = frame height, 70 cm = frame width, 64 cm = frame leg height, 60 cm = frame length, 60 cm = frame length, 83 cm = frame length. The automatic helmet dryer has proven effective in reducing humidity from 80% to 30% in 30 minutes. During the process, the temperature inside the helmet rises from 25°C to 35°C, thus accelerating the drying and showing a positive correlation between decreasing humidity and increasing temperature, Cost analysis calculation using BEP and NPV methods, namely, Investment cost = 3,550,000 can be met for 1.6 months calculated using the BEP method, the results of the NPV calculation in the 36th month produce Pv of proceed = 48,472,051. NPV of 44,922,571. NPV is positive, so the project proposal should be accepted. Keywords: Automation, BEP, NPV, QFD